THE DYNAMICS OF THE CLIMATIC CONDITIONS OF THE TEREK-KUMA LOWLAND DURING 120 YEARS - G. N. Gasanov; T. A. Asvarova; K. M. Gadjiev; A. S. Abdulaeva; Sh. K. Salikhov; R. R. Bashirov (Юг России: экология, развитие)
Abstract. Aim. This article is devoted to the analysis of climatic conditions of the territory of the Terek-Kuma Lowland. Data of the last 60 years (1951–2010) are compared with conditions of 1881–1935 (air temperature) and 1898–1948 (precipitation and relative humidity). Determination of tendencies in the age-old range, and for the last 60 years is given.Location. Terek-Kuma Lowland, Eastern Ciscaucasia, Russia.Methods. The following environmental parameters are characterized: the amount of monthly rainfall, average temperatures and humidity, evaporation, moisture ratio and the lack of moisture. Statistical characteristics (mean, variance, coefficient of variation) of annual precipitation, mean annual temperature and humidity, evaporation, lack of moisture are calculated. Separately, the same parameters were calculated for the warm (April – October) and cold (November – March) seasons. Significance of differences between them was assessed by the standard deviation (α) and the coefficient of variation (Cv).Results. Our analysis of the moisture conditions of the Terek-Kuma Lowland in the last 60 years has shown significant changes in key climate indicators in comparison with the corresponding (for the duration of observations) rates in preceding years. The average annual temperature for the period , including for the warm season (April – October), increased by 0.6 °C, annual precipitation decreased respectively by 29.6 and 35.9 mm. Coefficient of humidity (ratio of annual precipitation to evaporation) in the ambient range from 0.11 in 1898–1948 increased to 0.14 in 1951–2010.Conclusions. Aridity of the climate did not increase on this territory. In 1951–2010 coefficient of humidity increased to 0.14, and fits into the range for dry (arid) regions, while in 1898–1948 coefficient of humidity was 0.11 and it was an important characteristic of extra arid (very dry) areas.